Merlin's tour of the universe : a traveler's guide to blue moons and black holes, Mars, stars & everything far - Tyson, Neil deGrasse (Blackstone Publishing, 2024)
Merlin, a fictional timeless visitor from Planet Omniscia in the Andromeda Galaxy, has observed firsthand many of the major scientific events of Earth's history. In this journey through the cosmos, Merlin responds to popular questions asked by adults and children alike.